The Dream in the Prado Musem: Iconographic Problems - Carrasco Ferrer, Marta; Elvira Barba, Miguel Ángel (Eikón / Imago, 2016)
Hipno, in Latin Somnus, the Dream, is more a personification than a mythical figure, although it intervenes in certain legends. However, here we are interested because it appears in three sculptures of the Prado Museum, and each one of them poses different problems, both iconographic and historical. The present study analyzes separately in order to show how many approaches can be taken before the ideal sculptures of Roman times.